The Duties under the Doctrine of Superior Responsibility: What Can We Learn from Business Standards on Corporate Governance & Compliance? - Irakli Kvirikashvili (German Law Journal)
Given its role as a legal instrument not only to try superiors but also to prevent both them and their subordinates from committing grave international crimes, the correct understanding and proper application of the doctrine of superior responsibility is of paramount importance. This article aims to illuminate specific and some controversial aspects of the third element of the doctrine—the failure to adopt necessary and reasonable measures—and obtain a clearer and more comprehensive understanding on the superiors’ duties, its limits and main prerequisites under the doctrine. For this purpose, an interdisciplinary study was conducted to investigate whether basic principles and business aspects of corporate governance and compliance management may be applied for a better understanding and refinement of the doctrine. The underlying analysis in corporate governance and compliance covers American (U.S.), German, and international standards.